Nonfunctional paraganglioma of the head of the pancreas: A rare case report. (2016) - Ginesu, G.C.; Barmina, M.; Paliogiannis, P.; Trombetta, M.; Cossu, M.L.; Feo, C.F.; Addis, F.; Porcu, A.
Highlights: Pancreatic localization of paraganglioma is extremely rare (only 31 similar cases have been described in the scientific literature). Differential diagnosis with meningiomas, schwannomas, and various metastatic carcinomas may be challenging to assess preoperatively. Same management adopted for Pancreatic Neuroendocrine Tumors (NET) may be rational. Abstract: Background: Paragangliomas are rare neoplasms that originate from the neural crest. They are malignant in approximately 10% of cases, with a 50% survival rate at 5 years from diagnosis. In most cases, manifestations of malignancy (such as metastasis) are lacking, and paragangliomas are considered benign lesions. Pancreatic paragangliomas are extremely rare, with only 31 cases described in the scientific literature to date. Case summary: Here we describe a case of a 55-year-old Caucasian male patient referred to our institution in September 2013 for lumbar pain lasting five months. The ultrasound and the CT scan revealed a 2.5 cm solid nodule located in the uncinate process of the pancreas. On the basis of this evidence, the preoperative diagnosis was a pancreatic neuroendocrine tumor (NET), which was further confirmed by a subsequent In-Pentetreotide Scan examination. A pylorus-preserving duodenocephalopancreasectomy was performed. Pancreatic paraganglioma was the final pathological diagnosis. Rare localizations of paraganglioma are often discovered casually, during imaging examinations for other clinical reasons, as happened in the case of our patient. It appears evident that the preoperative diagnosis of pancreatic paragangliomas is extremely challenging. Surgery represents the cornerstone of the clinical management of these neoplasms, primarily for the need of a definitive diagnosis, which is difficult to assess preoperatively in most cases. Conclusions: Our strategy is the same as that adopted for the management of pancreatic NETs; the dimensional limit for a conservative resection is 2 cm, while major resections (Whipple's approach or distal pancreatectomy) should be employed in larger tumors, which are generally associated with a worse prognosis.